Associations Between Work Motivation and Quality of Anesthesia and Surgical Services: A National Cross-Sectional Study of Nurse Anesthetists in Indonesia - Richa Noprianty; Wahyu Wahdana; Asriadi Prihandika Widianto; Gina Sonia (Journal of Public Health and Pharmacy, 2026)
Introduction: The operating room consists of various health professionals so that they must build good teamwork to realize optimal anesthesia and surgical services. Therefore, it is necessary to have work motivation to be able to improve the quality of anesthesia and surgical services. The purpose of this study was to determine the components of work motivation in the operating room and anesthesia that can provide implications for anesthesia and surgical services. Methods: This type of research is quantitative with cross sectional. The sample used was nurse anesthetist who worked at the hospital, using accidental sampling so that a sample of 188 nurse anesthetists was obtained. The research instrument was a Motivating Potential Score (MPS) questionnaire and a surgical anesthesia service questionnaire from the Ministry of Health Accreditation Standards Year 2022 which was provided via google form. Data analysis using Spearman rank correlation coefficient. This research has obtained permission from the IPAI professional organization and is ethically feasible No. 209/09.KEPK/UBK/VIII/2024. Results: The results indicate that the average work motivation score was 9.86 (min 3.6; max 12), while the quality of anesthesia and surgical services averaged 14.31 (min 8.14; max 16). All components of work motivation: skill variety, task identity, job significance, autonomy, and feedback showed significant associations with service quality. Notably, autonomy demonstrated a moderate positive correlation with anesthesia and surgical service quality (r = 0.511, p < 0.001, 95% CI: 0,42-0,59), highlighting the magnitude of its effect and strengthening the analytical robustness of the findings. Conclusion: There is an influence of motivation on anesthesia and surgical services with a p value of 0.013 and a CC value of 0.181. Increasing conducive work motivation successfully provides satisfaction for nurse anesthetists and has an important role in quality anesthesia and surgical services.